Calculation of stress intensity factors of matrix crack tip in particle reinforced composites using the singular Voronoi cell finite element method. (June 2019) - Li, Huan; Guo, Ran; Cheng, Heming
Highlights: Extension to VCFEM is achieved through enhancements in stress functions. A singular Voronoi cell finite element method is proposed. Stress intensity factors of crack-tip are calculated using the least square method. Validation of this model shows good improvement. Abstract: In this paper, a new singular Voronoi cell finite element method (S-VCFEM) is proposed to study the initiation and propagation of interfacial debonding and matrix cracking in particulate reinforced composite. Composites with large-scale inclusions and cracks can be easily simulated with this model. A new assumed stress hybrid variational functional is derived from the element energy function to accommodate the interface traction reciprocity on bonded interface and the interface traction-free on debonded interface and matrix crack surface. S-VCFEM is achieved through enhancements in stress functions in the assumed stress hybrid formulation. In addition to polynomial terms and interaction terms, singular stress terms of Williams expansion are added for stress functions, which are adaptively enriched to accurately capture the crack-tip stress concentrations. After obtaining the stress field, calculation of stress intensity factors is performed, using the least square method based on stress value obtained numerically in the S-VCFEM. The efficiency of the method is verified against numerical results obtained by ABAQUS with XFEM module for the same problem considering a matrix-crack and a debonded interface.